APOBEC3B Gene Deletion Status inMultidrug-Resistant Tuberculosis(MDR-TB) Patients in Dr. MoewardiGeneral Hospital in Surakarta - Suryani, Fitri Ika; Prasetyo, Afiono Agung; ., Hudiyono (Nexus Biomedika, 2015)
Background: Data of APOBEC3B gene deletion status in Indonesia are limited. Moreover, information aboutAPOBEC3B gene deletion status in Multidrug-Resistant Tuberculosis (MDR-TB) patients in Dr. Moewardi General Hospital in Surakarta was unknown. This study was aimed to know the APOBEC3B gene deletion status in MDR-TB patients in Dr. Moewardi General Hospital in Surakarta. In the future, this research was expected can be used as asupporting examination in chronic tuberculosis patients which tend to progressively become MDR-TB. Methods: Blood samples from 43 MDR-TB patients in Dr. Moewardi General Hospital in Surakarta were collected, DNA isolation was performed for all samples, followed by a single Polymerase Chain Reaction (PCR)to detectthe presentation of APOBEC3B gene deletion genotype. Results: APOBEC3B gene deletion genotype was detected in81.4%(35/43) samples. Conclusions: The APOBEC3B gene deletion genotype was frequently found in MDR-TB patients in Dr. Moewardi General Hospital in Surakarta. Keywords: APOBEC3B, deletion, MDR-TB